Decrease of GSK-3β Activity in the Anterior Cingulate Cortex of Shank3b−/− Mice Contributes to Synaptic and Social Deficiency - Wang, Mengmeng; Liu, Xinyan; Hou, Yilin; Zhang, Haifeng; Kang, Junjun; Wang, Fei; Zhao, Youyi; Chen, Jing; Liu, Xufeng; Wang, Yazhou; Wu, Shengxi (Frontiers in Cellular Neuroscience, 2019)
Social deficiency is the core syndrome of autism spectrum disorders (ASD), about which the underlying developmental mechanism still remains elusive. Anterior cingulate cortex (ACC) plays a key role in integrating social information and regulating social behavior. Recent studies has indicated that synaptic dysfunction in ACC is essential for ASD social defects. In the present study, we investigated the development of synapses and the role of Glycogen synthase kinase 3β (GSK-3β), a molecular mediating multiple signaling pathways in synapses, in ACC by using a widely used ASD mouse model, Shank3b-/- mice. Our data revealed that Shank3b mutation abolished the social induced c-Fos expression in ACC. From 4 weeks old, Shank3b-/- mice exhibited obvious decrease of spine density and stubby spines. In addition, the length and thickness of post-synaptic density (PSD), the expression of vesicular glutamate transporter 2 (VGluT2) and GluR2 were significantly reduced in Shank3b-/-ACC. Interestingly, the levels of phosphorylated GSK-3β (Ser9) which inhibited the activity of GSK-3β decreased with a similar time course as the levels of GluR2 increased in ACC during development. Shank3b mutation leads to dramatic increase of phosphorylated GSK-3β (Ser9) and decrease of GluR2 in ACC. Local delivery of lentivirus expressing constitutively active GSK-3β restored the expression of GluR2, increased the spine density and the number of mature spines. More importantly, active GSK-3β significantly promoted the social activity of Shank3b-/- mice. These data, in together, indicated that decrease of GSK-3β activity in ACC may contribute to the synaptic and social defects of Shank3b-/- mice. Enhancing GSK-3β activity may be utilized to treat ASD in the future.